Experimental Research on the Similarity of Rime Icing on a Cylinder Rotating around Its Horizontal Axis - Lei Shi; Yan Li; Wenfeng Guo; Ce Sun (International Journal of Rotating Machinery)
Ice accumulation on the blade of a wind turbine surface seriously threatens the operational safety of the turbine; therefore, the research on this problem is very important. In this paper, a new similarity criterion of icing shape for a rotational model was proposed based on the similarity criterion for translational motion models in the aviation field, and experimental studies on the similarity of the rotational model icing were carried out. To validate the similarity criterion, icing wind tunnel tests were carried out with aluminum cylinders with diameters of 40 mm and 20 mm. Key parameters for the experiment, such as wind speed, temperature, liquid water content, medium volume diameter, and test time, were selected based on the criterion. All the icing tests were carried out in a new self-designed icing wind tunnel test system based on natural low-temperature conditions. The icing shapes observed in the tests were confirmed after many repetitions. To quantitatively analyze the similarity between different sizes of ice shapes, a dimensionless method for evaluating the similarity of ice shapes of different sizes was defined based on the typical characteristics of ice shapes. The research results show that the similarity score between two sizes of ice shapes under different test conditions is 81%~90%. The accuracy and applicability of the icing shape similarity criterion were thus validated. The research results in this paper lay a theoretical and experimental foundation for exploring the icing shape similarity of a rotating model.